4-Methylthio-3-butenyl isothiocyanate mediates nuclear factor (erythroid-derived 2)-like 2 activation by regulating reactive oxygen species production in human esophageal epithelial cells. (January 2018) - Hirata, Tadashi; Cho, Young-Man; Suzuki, Isamu; Toyoda, Takeshi; Akagi, Jun-ichi; Nakamura, Yasushi; Numazawa, Satoshi; Ogawa, Kumiko
Abstract: 4-Methylthio-3-butenyl isothiocyanate (MTBITC) extracted from daikon ( Raphanus sativus ), which shows antimutagenicity, may have applications as an effective chemopreventive agent in several cancers; however, few reports have described the associated mechanisms. We investigated whether MTBITC induced cytoprotective genes, including phase II enzymes, in Het-1A human esophageal epithelial cells. HMOX1, NQO1, and GCLC mRNA levels and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) protein levels were increased in Het-1A cells treated with 10 μM MTBITC. Reactive oxygen species (ROS) tended to increase when Het-1A cells were treated with MTBITC, and the increases in ROS and Nrf2 expression in the cells treated with MTBITC were completely abolished by treatment with N -acetyl-l -cysteine. We also examined the relationships between Nrf2 activation and mitogen-activated protein kinase (MAPK) signaling by western blot analysis. MTBITC induced extracellular signal-regulated kinase, c-Jun N-terminal kinase, and p38 phosphorylation in Het-1A cells; however, MTBITC did not affect the relationship between Nrf2 activation and MAPK responses. In the present study, we found that MTBITC induced Nrf2 activation and cytoprotective genes via ROS production in Het-1A cells. These results suggest that MTBITC may have the potential for preventing esophageal carcinogenesis through modification of carcinogen metabolism by phase II enzyme induction via ROS production. Graphical abstract: Highlights: MTBITC extracted from daikon ( Raphanus sativus ) has been expected to cancer chemopreventive agent. MTBITC induced Nrf2 activation, which plays pivotal roles in cytoprotection. The mechanism of Nrf2 activation induced by MTBITC are via increased level of ROS.